Constructing connections: urban forestry and Toronto’s West Don Lands revitalization - Nichols, Paul (Environnement Urbain / Urban Environment)

(untitled) (Réseau Villes Régions Monde, 2009)
AbstractThe West Don Lands played an important role in Toronto’s history, primarily as an industrial centre from the mid-19th century to the mid-20th century. Therefore, the negative impacts of de-industrialization on the precinct can hardly be considered surprising. However, efforts are being made to revitalize the West Don Lands and redress the decay experienced by the precinct. This paper examines these efforts, detailed in the Waterfront Toronto’s Precinct and Block Plans, with particular focus being placed on the role that urban forestry can play on the creation of physical and social linkages.